The human tutorial dialogue project : issues in the design of instructional systems - Fox, Barbara A. (Computers, cognition, and work., 1993)
This volume's goal is to begin to document the dialogue processes in naturally-occurring human tutoring, in the context of informing the design of intelligent tutoring systems and of interactive systems in general. This project represents the first empirical study of human tutorial dialogue from a conversation analytic perspective - the conversational interaction is the focus of analysis rather than larger scale techniques for teaching. It is also the first study of tutoring to make use of large quantities of carefully transcribed tutoring conversations/dialogues.